Entrepreneurship in Tourism: a bibliometric analysis of components and trends in business models - Garcia Reinoso, Nelson (2024)
The literature shows multiple bibliometric studies on business models across various sectors; however, little attention has been paid to the systematic analysis of academic production in tourism entrepreneurship. The business model in these ventures is a complex process involving sustainable practices and exchanging knowledge and resources within the entrepreneurial ecosystem. Entrepreneurs in tourism often have limited management and organisational capabilities due to an insufficient understanding of the components of business models and their interrelationships in fostering innovation and sustainability. This paper aimed to analyse the lack of unified definitions regarding business models in tourism entrepreneurship and provide guidelines for developing new models and managing existing ones. Through an analysis of 71 articles published between 2000 and 2022, 14 key components were identified and grouped into three main functions: value proposition, value creation and delivery, and value capture. It is concluded that integrating these elements is essential to optimise competitiveness and sustainability and drive innovation and sustainable growth in the tourism sector.